Desain Aplikasi Mobile Berbasis Android Untuk Menerapkan Model Pembelajaran Flipped Classroom Mata Kuliah Bahasa Inggris - Sampebua, Abigael; Sampebua, Mingsep Rante (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The ability to master and understand English, for example, in reading, writing, listening and speaking is still a big obstacle faced by students of the English Language study program at Universitas Persatuan Guru 1945 NTT. This is caused by the implementation of a learning system that is still centered on lecturers as instructors. As a result, the learning process occurs only in one direction and is not interactive because students tend to only listen to the lecturer's explanation and be passive. Also, students become unable to focus so they experience difficulty in developing the ability to respond to the material received and develop innovative creative ideas independently. This research aims to design and develop an Android-based mobile application as a learning medium that can be integrated into the flipped classroom model in English courses. This mobile application development uses the waterfall method comprising five stages, namely identifying user needs, analysis, design, implementation and testing. This research resulted in the development of an Android-based mobile application as a learning medium that applies the flipped classroom model which is used to change the learning style to be more student-centered so as to provide an interesting learning experience